Monetary policy of NBS and convergence to EMU - Čačková, Anna; Durčáková, Jaroslava, 1941-; KUNZ, Tomáš; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2009)
Diploma thesis is entitled Monetary policy of NBS and convergence to EMU. Introductory theoretical section describes the development of monetary unions in the past and the causes of their extinction. Subsequently, it is devoted to the foundation of the European Monetary Union in various stages, of its crisis and transition to the ERM II exchange rate system. It characterizes the nominal Maastricht criteria in theory. Following chapters constitute the practical part of the thesis. Chapters 2-4 discuss the monetary policy of the NBS and its roles and objectives. They outline monetary policy of NBS in the individual periods followed by an evaluation of measures and compliance with the main objectives, such as exchange rate stability, inflation targeting and inflation targeting in ERM II. The last chapter discusses the costs and benefits of euro, their comparison and evaluation of the appropriateness of the timing of entry into EMU. Real convergence is emphasised and represented by GDP per capita, the adjustment of price levels, employment and foreign trade. Nominal convergence is represented by Maastricht convergence criteria and their implementation. The development of various criteria is compared with the countries of V4 -- Czech republic, Poland and Hungary. Finally it summarises the overall functioning of the National Bank in the field of monetary policy, the appreciation of the euro advantages and appropriateness of the timing.
Vedoucí práce: Jaroslava Durčáková
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2010
Rok obhajoby 2010
Keywords: finance [obor dipl. práce]; euro; diplomové práce; euro; master's theses